2023
DOI: 10.3389/fdata.2022.971974
|View full text |Cite
|
Sign up to set email alerts
|

Sharing social media data: The role of past experiences, attitudes, norms, and perceived behavioral control

Abstract: Social media data (SMD) have become an important data source in the social sciences. The purpose of this paper is to investigate the experiences and practices of researchers working with SMD in their research and gain insights into researchers' sharing behavior and influencing factors for their decisions. To achieve these aims, we conducted a survey study among researchers working with SMD. The questionnaire covered different topics related to accessing, (re)using, and sharing SMD. To examine attitudes toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Our study is also in line with Akdeniz et al (2023), who found that while altruistic motives like contributing to open science and transparency were pivotal in sharing decisions, practical concerns like legal restrictions and ethical considerations also played a significant role. Such insights are crucial in understanding the dynamics of data-sharing behavior.…”
Section: Attitudinal Factorssupporting
confidence: 90%
See 1 more Smart Citation
“…Our study is also in line with Akdeniz et al (2023), who found that while altruistic motives like contributing to open science and transparency were pivotal in sharing decisions, practical concerns like legal restrictions and ethical considerations also played a significant role. Such insights are crucial in understanding the dynamics of data-sharing behavior.…”
Section: Attitudinal Factorssupporting
confidence: 90%
“…For example, Sommestad et al (2015) used the TPB to explain policy compliance intentions in information security and showed that the TPB made good predictions. Akdeniz et al (2023) used the TPB and identified critical factors influencing intentions to share social media data, including past experiences with data sharing, attitudes towards sharing, perceived norms, and perceived behavioral control.…”
Section: The Theory Of Planned Behaviormentioning
confidence: 99%
“…Compared with data obtained from traditional surveys, tourist attraction name data on social media not only provide the possibility of researching a wide range of topics but also allow for the investigation of research questions with large samples. Compared with survey data, they can be monitored continuously for a long time (and with high temporal resolution) at a lower cost [6]. After analyzing and being inspired by previous research, this paper proposes a Chinese tourist attraction toponym extraction model based on RoBERTa-BiLSTM-CRF [7].…”
Section: Introductionmentioning
confidence: 99%